(untitled) (Journal of Engineering, 2011)
Friction stir welding (FSW) is a relatively new welding process that may have significant advantages compared to the fusion processes as follow: joining of conventionally non-fusion weldable alloys, reduced distortion and improved mechanical properties of weldable alloys joints due to the pure solid-state joining of metals. In this paper, a two-dimensional model based on finite element analysis is used to study the thermal history and thermomechanical process in the butt-welding of aluminum alloys. The model incorporates the mechanical reaction of the tool and thermomechanical process of the welded material. The heat source incorporated in the model involves the friction between the material and the probe and the shoulder. The calculation result also shows that preheat to the workpiece before process is beneficial to FSW. The effects of welding parameters such as preheating (100, 200) °C, rotational speed (960, 1200) rpm and linear speed (110, 155, 195) mm/min on the distribution of temperature of Al Alloy will be studied.